2nd International Conference on Innovative Sciences and Technologies for Research and Education (InnoSTRE) 2022 "Probing the societal challenges through a unified, interdisciplinary'platform" - Abdullah, Firdaus; Khong, Heng Yen; Yee Hui, Robin Chang; Ha, Chiew Fei; Lau, Ung Hua; Darham, Widyani; Abdul Rashid, Ahmad Faiz; Nyuin, Joe Davylyn (2022)
Angiogenesis is the process of new blood vessel development from the existing vasculature. It occurs throughout life in both healthy and diseased individuals, from conception to old age. Angiogenesis is tightly regulated in the healthy adult human body. It is regulated by a variety of endogenous angiogenic and angiostatic factors. Unregulated angiogenesis plays critical in majority of human diseases. This can cause pathological conditions such as cancer, heart disease, chronic degenerative disorders such as Alzheimer disease, obesity, eye diseases and many more. Natural products have anti-oxidant and anti-inflammatory properties which can potentially modulate angiogenesis process making them useful in treating diseases which are angiogenesis dependent. Natural herbal medicines, which have the advantages of being multitarget and polymolecular with fewer side effects and lower in cost, are attracting increasing attention as therapeutic agents to treat or manage diseases which are angiogenesis dependent.